THE EFFECTIVENESS OF GUESSING WORD IN TEACHING SPEAKING TO THE EIGHTH GRADE STUDENTS OF MTS NURUSSALAM OKU TIMUR - Sri Hartati; Andriyani . (Jurnal Didascein Bahasa, 2018)
This study was conducted to find out whether or not it was effective to use guessing words in teacing speaking to the eighth grade students of MTs Nurussalam OKU Timur. Pre experimental was used in this study, with 33 students chosen as the sample by using convenience sampling. The data obtained were statistically analyzed by using t-test. The result of the pair sample t-test showed that the value of t-obtained was 4.635, where the critical value was 2.035 at the significant level ɑ = 0.05 and degree of freedom was 32. Since the t-obtained was higher than the critical value, the null hypothesis (Ho) was rejected and alternative hypothesis was accepted. It could be concluded that it was effective to use guessing words in teaching speaking to the eight grade students of MTs Nurussalam OKU Timur. This is also implies the guessing words game expected to enhance students‘ motivation and interesting in learning activities, so they can improve their speaking achievement.Keywords: Teaching, Speaking, and Guessing Words.